Torbiele pajęczynówki u noworodków - opis 4 przypadków - Lisowska-Mikołajków, Dorota; Mikołajków, Agata; Reczuch, Jędrzej; Królak-Olejnik, Barbara (Pediatria Polska - Polish Journal of Paediatrics, 2017)
Arachnoid cysts are one of the endocranial pathologies occurring between dura mater of cerebrum and cerebellum and pia mater. The symptoms of arachnoid cysts depend on their size and localization. Small cysts are usually asymptomatic or present mild symptoms. Vast cysts cause mass effect, create pressure, displace surrounding tissues, and increase intracranial pressure, which may lead to neurological symptoms. The most common localization of cysts is in the middle and posterior cranial fossa in the natural reservoirs of cerebrospinal fluid. They may be diagnosed in the prenatal period or accidentally after birth. They may grow fast or diminish slowly or even disappear. Even neurological symptoms of the vast cysts are unspecific. This review is based on 4 case reports of patients diagnosed with arachnoid cysts in the Department of Neonatology in the years 2015-2016. This review will present diagnostic and therapeutical procedures, and in some cases neurological follow-up.